The boundary condition simulation quality for embankment seismic response. (August 2021) - Namdar, Abdoullah
Highlights: The seismic boundary condition for the embankment was investigated. The low-rise and high-rise embankments were modeled. The seismic load was applied on the model in single and multidirectional. The nonlinear displacements for all models were analyzed. The statistical analysis was applied to evaluate the results. Abstract: To solve a nonlinear engineering problem, the numerical simulation faces limitations in developing appropriate boundary conditions. Applying seismic load to the model in a single direction is not a proper boundary condition for embankment seismic stability assessment, and also for solving other nonlinear engineering problems are subjected to multidirectional dynamic loads simultaneously. In this study, the application of nonlinear numerical simulation for embankment-subsoil seismic assessment was investigated based on simulate accurate multidirectional seismic loads was applied to the model, while in the literature only horizontal seismic load was applied to the model. In this study, two basic models including low-rise and high-rise embankments have been modeled, and the seismic load was applied to the model in single and multidirectional in two independent numerical simulations. The strain, stress, and displacement for all models were analyzed. The maximum strain, stress, and displacement of the several stages of numerical simulation are extracted out for developing statistical analysis and simulate of the strain density, stress, and nonlinear displacement mechanism. To examine the quality of numerical simulation outcomes, the statistical model and analysis of all models have been compared. The statistical results show, applying multidirectional seismic loads to the embankment-subsoil model has better results quality for all low-rise and high-rise embankment compared to applying seismic load to the model in a single horizontal direction. The outcome of this study improves the application of the numerical simulation quality for prediction and assessment of the embankment-subsoil model seismic failure mechanism and all nonlinear engineering problems, through enhancement boundary conditions which are required according to literature analysis.